Disability and functioning in primary and secondary hip osteoarthritis in Benin........ - Todègnon, F; Assogba1, F; Niama-Natta, Didier D.; LAWSON 1, Teefany; KPADONOU GODONOU, TOUSSAINT; Mahaudens, Philippe; Detrembleu, Christine (My University, 2020)
Background: In Africa, primary hip osteoarthritis seems to be less frequent than in Europe. Sickle cell disease is responsible for aseptic osteonecrosis of the femoral head associated with secondary hip osteoarthritis. Very little evidence is available on the influence of aetiology (primary and secondary) and radiographic status on pain and disability in a Beninese population with hip osteoarthritis. Objectives: The aim of this study was to compare the impacts of aetiology and radiographic status on pain, disability and quality of life in a Beninese population with hip osteoarthritis. Method: This was a descriptive cross-sectional study, including participants recruited in the Clinic of Physical Medicine and Rehabilitation at the National Teaching Hospital in Cotonou. Assessment was based on the International Classification of Functioning, Disability and Health model. The main outcomes were severity of osteoarthritis, pain, range of motion, muscle strength, gait speed and quality of life. Statistical comparisons between the aetiologies were performed using a t-test or rank sum test. One-way analysis of variance was used to test the effect of radiographic status. Results: Forty-nine participants (26 women and 23 men; mean age [standard deviation] 40.5 [17.9] years) were recruited. According to the aetiology (59.2% and 40.8% of primary and secondary osteoarthritis, respectively), there were no significant differences for any of the outcomes. Grades I, II, III and IV osteoarthritis were observed in 22.4%, 14.3%, 26.5% and 36.7% of the participants, respectively. Participants with grade IV osteoarthritis were more affected than those with grades I, II and III based on the Kellgren and Lawrence classification. Conclusion: Aetiology did not influence pain, gait speed or quality of life. Participants with grade IV osteoarthritis had more pain, were more limited in walking and had a more impaired quality of life.
Keywords: Keywords: hip osteoarthritis; pain; gait speed; quality of life; Africa.